2014
DOI: 10.1155/2014/242703
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine-Induced Acute Pulmonary Edema: A Rare but Severe Complication of Tocolysis

Abstract: We report four cases of acute pulmonary edema that occurred during treatment by intravenous tocolysis using nicardipine in pregnancy patients with no previous heart problems. Clinical severity justified hospitalization in intensive care unit (ICU) each time. Acute dyspnea has begun at an average of 63 hours after initiation of treatment. For all patients, the first diagnosis suspected was pulmonary embolism. The patients' condition improved rapidly with appropriate diuretic treatment and by modifying the tocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…Combination therapy with magnesium sulfate or simultaneous administration of corticosteroids to induce fetal maturation are even more causative of pulmonary edema [ 2 ]. A report of pulmonary edema caused by calcium blockers such as nicardipine has also been published [ 9 ]. In our case, ritodrine hydrochloride and magnesium sulfate administration increased fluid volume, which may have caused overhydration.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy with magnesium sulfate or simultaneous administration of corticosteroids to induce fetal maturation are even more causative of pulmonary edema [ 2 ]. A report of pulmonary edema caused by calcium blockers such as nicardipine has also been published [ 9 ]. In our case, ritodrine hydrochloride and magnesium sulfate administration increased fluid volume, which may have caused overhydration.…”
Section: Discussionmentioning
confidence: 99%
“…Nicardipine treatment as a tocolytic has side effects, such as hypotension or maternal pulmonary edema [ 3 ]. Especially, pulmonary edema after use of nicardipine is mainly associated with preterm labor, and it is a severe complication for which the patients needed hospitalization in an intensive care unit [ 15 ]. Thus, limiting the dosage to what is needed to achieve the effective concentration for uterine relaxation and to avoid maternal complications is important.…”
Section: Discussionmentioning
confidence: 99%
“…Biological and radiological investigations have been performed to rule out the possibility of infection causing preterm labor, pulmonary embolism and a decompensated cardiac disease during pregnancy causing dyspnea. The clinical presentation of this complication following tocolysis with nicardipine is not specific, for this reason some authors have suggested B-type natriuretic peptide measurement for early diagnosis and monitoring of pregnant women with acute pulmonary edema [10]. The treatment of the APE induced by nicardipine is based on discontinuation of the tocolytic agent and symptomatic treatment based on the Oxygen Therapy and diuretics.…”
Section: Discussionmentioning
confidence: 99%